FIELD GEOLOGY AND ECONOMIC ASSESSMENT OF A MINERALIZED BARYTE VEIN IN TOLA, MAYOBELWA AREA, NORTHEASTERN NIGERIA - HALILU, MAIMUNA (IJRDO-Journal of Applied Science, 2017)
Investigations were undertaken for baryte mineralization in the Tola area of Northeastern Nigeria. The area is underlain by granite gneisses, porphyritic granites and alluvial deposits with granites and its porphyritic variants being the most dominant rock type. The mineralization is known to occur as fracture in filling in granitic and gneissic rocks of the Precambrian basement. Preliminary assessments of rock cuts from the vein showed the baryte to be of quality high enough to warrant further studies.